Sistem deteksi kemiripan judul skripsi dengan metode term weight dan word embedding - Selma Maharani; Firdiyan Syah; Nurirwan Saputra (Jurnal Dinamika Informatika, 2022)
The problem of plagiarism in education is ethics in writing [1]. Plagiarism is an act of taking ideas or words from abstracts, research proposals, whether published or not, whether printed or electronic [2]. A system for determining the level of similarity of student thesis titles is needed. Term Weight and Word Embedding methods and PHP programming, MySQL database for web-based Yogyakarta PGRI University. The object of this research is the thesis title as the independent variable and the title similarity level as the dependent variable. The results of the program display test showed that 27% of the respondents answered that it was very interesting, 60% of the respondents answered that it was interesting, and 13% said that it was not very interesting. The trial results regarding the ease of using the program obtained 50% of respondents answered very easily, 40% of respondents answered it was easy, and 10% of respondents answered it was not easy. The test results regarding program performance obtained the following data: 23% of respondents answered very well, 67% of respondents answered good, and 10% of respondents answered not very well. The trial results regarding the benefits of the program for users showed that 54% of respondents answered that it was very useful, 43% of respondents answered that it was useful, and 13% of respondents answered that it was not very useful.